INFLUENTIAL FACTORS OF THE SUCCESS AND/OR FAILURE OF DENTAL IMPLANTS - Fetco Andrei; Zanoaga (Afloarei); Tibeica Andreea; Cretu Cosmin; Curca Razvan; Agop-Forna Doriana; Norina Forna (Romanian Dental Association for Education, 2023)
Aim and objective of the study. Dental implants have emerged as new treatment modality for the majority of patients and are expected to play a significant role in oral rehabilitation in the future. The present study was conducted to assess various factors affecting the survival rate of dental implants. Objective: Evaluate the factors that influence the success and/or failure of dental implants.(5) Material and methods. This research is framed within a systematic bibliographic review. Results. The factors that have the greatest influence and affect the immediate result are heavy smoking, implant placement under a torque of less than 15 Nm, overheating of the site, lack of primary stability at the time of implant placement, premature loading or microbiological contamination that alter the normal healing process of the soft tissues and prevent the intimate union between the bone and the implant from forming.(5) Within the limitations of the present prospective clinical comparative study, peri-implant probing depth and marginal bone level around dental implants placed in edentulous sites in molar/premolar region were affected by different neck designs. Patients who received implants with rough wide-neck design presented lower probing depth and minor marginal bone loss compared to patients with rough reduced-neck implants. Reduced-neck implants showed a tendency to lose comparatively more bone over time if compared with wide-neck implants. However, dental implants' survival rate was acceptable and satisfactory for both groups of patients and showed no differences at the two-year follow-up. (4,19) Conclusions. Dental implants are not always successful. There is a 5-10% chance that they might fail. Among the many factors that can cause an implant to fail, some common ones are health conditions, age, smoking habits, poor oral hygiene, and insufficient jaw bone. Taking care of your oral health and following your dentist's advice can help you avoid some complications. Careful planning helps to reduce the risk of post-surgical implant failures.(6,15) Success and failure are dynamic conditions linked to time and require periodic evaluation. The main criteria to evaluate the quality of health of the dental implant are mobility and pain, the presence of any of them compromises the implant to a great extent. Non-osseointegration and peri-implantitis were the most frequent causes of failure in the initial phase of the treatment. Regarding the anatomical regions of the oral cavity, the failure rates were low and the survival and success rates were high.(1,15)